REGIONAL PRACTICE OF TAX REVENUE MANAGEMENT - S. N. Rukina; K. A. Gerasimova; A. S. Takmazyan; K. N. Samoilova (Вестник университета, 2020)
The debatable issues of forming a comprehensive system of tax revenue management, including tax and budget components in the Rostov region have been considered. It has been concluded about the priority of the tax component, which is based on the legally established tax powers of sub-Federal authorities in relation to regional taxes, corporate income tax, simplified taxation system and patent taxation system. Specified systems are characterized by instability and limitation. The analysis of the content of the tax authorities of the Russian Federation subjects and their interaction with tax expenditures, which provide a relationship with the goals of state programs, allowed us to substantiate proposals to expand the tax independence of the Russian Federation subjects for the period of implementation of national goals.